2020
DOI: 10.1136/bmjopen-2019-034529
|View full text |Cite
|
Sign up to set email alerts
|

Differences in medication beliefs between pregnant women using medication, or not, for chronic diseases: a cross-sectional, multinational, web-based study

Abstract: ObjectivesTo assess whether medication beliefs differ between women who use or not use medication for their somatic chronic diseases during pregnancy and whether this association varies across diseases.DesignCross-sectional web-based survey.SettingMultinational study in Europe.ParticipantsPregnant women or women with children less than 1 year old from European countries and with asthma, allergy, cardiovascular, rheumatic diseases, diabetes, epilepsy and/or inflammatory bowel diseases (IBD).Primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(52 reference statements)
1
7
0
1
Order By: Relevance
“…Within the current review, eight studies reported using theory or evidence to develop their intervention. Previous studies have identified factors that may influence medication adherence in pregnancy including sociodemographic characteristics [ 2 ] and beliefs about medications such as concerns or decreased belief that medication is beneficial or necessary [ 58 ]. In addition, women with chronic illness report receiving inconsistent information about medicines during pregnancy and breastfeeding [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within the current review, eight studies reported using theory or evidence to develop their intervention. Previous studies have identified factors that may influence medication adherence in pregnancy including sociodemographic characteristics [ 2 ] and beliefs about medications such as concerns or decreased belief that medication is beneficial or necessary [ 58 ]. In addition, women with chronic illness report receiving inconsistent information about medicines during pregnancy and breastfeeding [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Addressing patients concerns regarding possible teratogenic effects of ICS and ICS/formoterol reliever therapy during pregnancy is important. Positive medication beliefs are associated with better adherence [48]. While a recent study in pregnant asthma patients found that non-adherence was not associated with more concerns about ICS use during pregnancy, women who were adherent during the study were more likely to see the benefit of their asthma medication [49].…”
Section: Behavioral Traitsmentioning
confidence: 99%
“…11 Decisions about medication use and breastfeeding are particularly relevant for the 10%-20% of mothers who live with a chronic condition, [12][13][14] most of whom require medication use to manage symptoms and maintain quality of life. 15,16 These women may face uncertainty in weighing the benefits of continued medication use and breastfeeding with the potential risks of medication transfer to their child. Pharmacotherapy for the management of chronic conditions generally declines during pregnancy and remains low during the postpartum period, 17 suggesting that some mothers perceive the risks of medication use to outweigh the benefits and forego medications in order to breastfeed their child.…”
Section: Introductionmentioning
confidence: 99%
“…Decisions about medication use and breastfeeding are particularly relevant for the 10%–20% of mothers who live with a chronic condition, 12–14 most of whom require medication use to manage symptoms and maintain quality of life 15,16 . These women may face uncertainty in weighing the benefits of continued medication use and breastfeeding with the potential risks of medication transfer to their child.…”
Section: Introductionmentioning
confidence: 99%